Mechanical Behavior of Chain-Link Wire Nets under Pressure from a Warhead: Quasistatic Experiments and Simulations - Min Wang; Shuai Zhou; Qilin Huang (Modelling and Simulation in Engineering)
Wire nets woven from high-strength steel wires have been used as applique armor against attack by short-range weapons. In this study, the mechanical behavior of chain-link wire nets under pressure from a warhead was investigated by quasistatic experiments and simulations. First, the new rig, the warhead device, and the wire nets were designed; pressure tests were conducted; and the deformation, fracture of the wire nets, and pressure force vs. displacement curves were obtained and analyzed. Then, the numerical approach and Finite element (FE) model were developed, considering the contacts between the steel wires in the inner connections, the contacts between the warhead and the mesh of the wire nets, and the fracture of the steel wire material. By comparison with the experimental data, the numerical approach and FE model are shown to be reliable in predicting the behavior of the wire nets under pressure from a warhead. Finally, the parameters of the wire net size and the mesh angles were further investigated by using the validated numerical approach and FE model, and suggestions for the initial design of the wire nets are discussed.